Desbalanço superóxido-peróxido de hidrogênio versus seleno-L-metionina e castanha-do-Brasil: regulação diferencial in vitro de (seleno)enzimas - Schott, Karen Lilian (2017)
Introduction: The coupled enzymatic reactions between the manganese-dependent superoxide dismutase (MnSOD/SOD2) and selenoenzyme glutathione peroxidase-1 (GPx-1) selenoenzyme are essential for mitochondrial redox balance in aerobic cells. SOD2 dismutates the superoxide anion (O2 ) to hydrogen peroxide (H2O2) which is reduced to water by GPx-1. At low concentrations, reactive oxygen species (EROs) O2 and H2O2 are essential for the maintenance of the body's homeostasis. However, in the single nucleotide polymorphism (SNP) in the gene that codes for SOD2 (Val16Ala-SOD2) the AA genotype is 30-40% more efficient than the wild VV causing a superoxide (S)-hydrogen peroxide (HP) imbalance, associated to development of chronic noncommunicable diseases. The VV genotype was associated with cardiometabolic diseases and metastatic breast cancer. Whereas, AA genotype have been related to an increased risk of breast, prostate and colorectal cancer, suggesting that the excess of H2O2 generated could be higher than the antioxidant capacity of GPx-1. In addition, a previous study showed that the risk of breast cancer decreased in an expressive manner in women carriers of AA genotype who reported a diet rich in fruits and vegetables. However, the potential benefic effect of Brazil nut, rich in seleno-L-methionine (SeMet) and antioxidant phytochemicals, on the regulation of cellular oxidative metabolism had not yet been investigated. To test this hypothesis, we aimed to perform a literature review work about brazil nuts and, in parallel, to evaluate the influence of the genetic and chemically induced S-HP imbalance on the in vitro effect of the purified SeMet and that contained in the Brazil nut aqueous extract (BNAE), through the analysis of antioxidant enzymes modulation and other variables. Methods: In the Protocol 1, peripheral blood mononuclear cells (PBMC) were genotyped for the Val16Ala-SOD2 polymorphism and treated with purified SeMet for 24 h in RPMI cell culture medium. In the Protocol 2, HFF-1 fibroblasts were S-HP chemically imbalanced with MnTBAP (AA-SOD2-like) and Paraquat (VV-SOD2-like) and after treated with Brazil nut aqueous extract (BNAE) for 24 h in DMEM 15% medium. In the both protocols, cellular growth and ROS production were evaluated using concentration-effect curves in PBMC (SeMet (0; 1; 3; 10; 30; 100; 300 e 1000 nM)) and in HFF-1 fibroblasts (MnTBAP and Paraquat (0, 0.01; 0.03; 0.1; 0.3; 0.9 μM), and Se in the BNAE (0; 1.25; 2.5; 25; 50; 75; 100; 125 ng Se/ mL BNAE)). The effective concentration was used to evaluate gene expression of antioxidant enzymes CuZnSOD (SOD1), SOD2, GPx-1, thioredoxin reductase (TrxR) and catalase (CAT), and oxidative metabolism parameters in both. Evaluation of the activity of antioxidant enzymes, 8-hydroxy-2’-deoxyguanosine (8-OHdG) and apoptosis was performed only in Protocol 1. Results: Effective concentrations of SeMet, MnTBAP and / or Paraquat and Se in the BNAE were 1 nM; 0.9 μM and 75 ng Se / mL, respectively. The regulation of gene expression was differential between protocols 1 and 2, whereas general oxidative parameters decreased in both protocols. In the Protocol 1, relative to negative control, CMSP treated with 1 nM purified SeMet decreased apoptosis, 8-OHdG and CAT expression in all genotypes, but CAT activity decreased only in AA genotype. In the AA-PBMC, SOD expression and activity increased. Gene expression of GPx-1 unchanged and TrxR-1 decreased expressively while GPx-1 and TrxR-1 activities were modulated positively. In the VV-PBMC, the expression of all enzymes decreased, except for TrxR-1. Positive activity modulation was observed for GPx-1, TrxR-1 and CAT but negative for SOD. In the Protocol 2, BNAE- treated fibroblasts AA and VV-SOD2-like increased CAT gene expression following SOD2 standard. SOD1 and GPx-1 decreased while TrxR-1 and CAT increased in AA-SOD2-like. Positive modulation of activity was observed for GPx-1, TrxR-1 and CAT but negative for SOD. In the Protocol 2, AA and VV-SOD2-like fibroblasts treated with BNAE increased CAT gene expression following SOD2 standard. SOD1 and GPx-1 decreased while TrxR-1 and CAT increased in AA-SOD2-like. Diversely, in BNAE- treated VV-SOD2-like, expression of SOD1, GPx, and CAT increased, whereas TrxR-1 unchanged. In general, results showed a compensatory and nutrigenetic effects in the PBMC treated with purified SeMet, while imbalanced S-HP fibroblasts treated with SeMet associated to the chemical matrix of BNAE showed synergistic and nutrigenomic effects.